Competencias interculturales y comprensión lectora en estudiantes del CECIB “provincia de sucumbíos”, la dolorosa – Achupallas. - Dina Judith, Valente Balla (2021)
ABSTRACT This research work analyzes two variables: intercultural competencies and reading comprehension. The main objective was to determine which intercultural competencies influence the students' reading comprehension of the sixth and seventh years of primary general education in the CECIB Province of Sucumbíos, La Dolorosa-Achupallas. The researcher used dynamic activities that promote intercultural dialogue and respect for cultural diversity. A qualitative-quantitative approach methodology was used. There was an approach to study and naturally interpreted the phenomenon, based on the meaning that it assigns through data collected in the observation sheet are quantified, likewise with the survey and test to demonstrate the results in the application of the pedagogical guide. The observation allowed the analysis of the students' behavior since within the teaching process, there was significant participation both individually and in groups; Likewise, the application of the anonymous survey made it possible to collect relevant information for the strengthening of the didactic guide. It should be noted that the test evidenced the level of learning that students achieved in intercultural competencies and reading comprehension, measuring the academic performance of these students through their grades. It was concluded that reading comprehension from different activities that show intercultural competencies gives rise to the knowledge of texts that are instruments of great importance for developing reading skills. Keywords: Intercultural competencies, reading comprehension, reading, interculturality. Reviewed by: Dr. Narcisa Fuertes, PhD. ENGLISH PROFESSOR Cc: 1002091161